Practicality of the RODE Learning Model in Order to Improve Student Communication Skills - Arief Ertha Kusuma; Wasis Wasis; Endang Susantini; Rusmansyah Rusmansyah (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
The RODE Learning Model is designed to improve student's communication skills. The RODE learning model has four stages: Read, Outline, Discussion and Evaluation. This study aims to analyze the practicality of the RODE learning model in improving student communication skills in elementary school 2 science lectures involving 50 students as a research sample. The research data were collected using an instrument of observation sheets on the implementation of learning and observation sheets of student activities which were assessed by two observers and equipped with a record of obstacles encountered during the application of the RODE learning model. Data analysis techniques use quantitative and qualitative descriptive analysis. The results showed that the four stages of the model, namely Read, Outline, Discussion, and Evaluation, can be carried out correctly and reliably, and there are no obstacles that cannot be overcome. In general, student activities relevant to the RODE learning model have increased in each meeting. So it can be concluded that the RODE learning model is practical because it can be carried out according to the lecture implementation plan, and student activities are relatively active. The obstacles that arise can be overcome properly.